Tug‐of‐War between Two Distinct Catalytic Sites Enables Fast and Selective Ring‐Opening Copolymerizations - Wang, Jianqun; Zhu, Yinuo; Li, Maosheng; Wang, Yanchao; Wang, Xianhong; Tao, Youhua (Angewandte Chemie International Edition, 2022)
Ring‐opening copolymerizations have emerged as a powerful approach towards the creation of sustainable polymers. Typical H‐bonding catalysts for ring‐opening are subject to a single catalytic site. Here we describe a H‐bond‐donor/Lewis‐acidic‐boron organocatalyst featuring two distinct catalytic sites in one molecule. The ring‐opening copolymerization of epoxides with anhydride mediated by these modular, and tunable catalysts achieves high selectivity (>99 % polyester selectivity) and markedly higher activity compared to either of the di‐thiourea analogues or any combinations of them. Calculations and experimental studies reveal that the superior catalytic performance arises from tug‐of‐war between two differentiated catalytic sites: thiourea pulls off the propagating chain‐end from boron center, simultaneously enhancing the role of monomer activation and also nucleophilicity of the propagation intermediates. The power of organocatalysts featuring two distinct catalytic sites in one molecule was illustrated in the ROCOP of epoxides with anhydride, giving excellent selectivity and activity. A chain tug‐of‐war mechanistic pathway is proposed to rationalize the simultaneous enhancement in monomer activation and nucleophilic attack, thus giving rise to outstanding catalytic performance.